Numerical Simulation of Heat Transfer Coefficient and Film-Cooling Performance Influenced by the Orientation of Internal Turbulence Promoting Ribs - Yukiko AGATA; Toshihiko TAKAHASHI; Eiji SAKAI; Koichi NISHINO (Journal of Thermal Science and Technology, 2013)
Heat transfer coefficient and film-cooling performance have been studied numerically by using the detached eddy simulations. The detailed characteristics of heat transfer coefficient influenced by the orientation of internal turbulence promoting ribs are examined. The heat transfer coefficient and the adiabatic film cooling effectiveness reported previously are discussed with relation to the flow structures of the film-cooling air. Those simulation results are combined to evaluate the net heat flux reduction and the net surface temperature reduction. The effects of the rib orientation on the evaluated film-cooling performance are discussed based on the flow structures. The present results have demonstrated the significant effects of the rib orientation on the film-cooling performance of gas turbine blades.